Prediction of unconfined compressive strength of pulverized fuel ash-cement-sand mixture - Motamedi, S.; Song, K.I.; Hashim, Roslan (2013)
Recently, ground improvement has become much more feasible. Chemical stabilization is a quick and affordable approach to enhancing soil characteristics. An important avenue of research is discovering alternative materials for use in soil enhancement. Pulverized fuel ash (PFA), which is a waste byproduct of coal power plants, has been shown to reduce the environmental risks and costs involved in construction. In this study, a series of unconfined compressive tests were performed for various mixtures of cement, PFA, and sand; the tests considered both the curing period and the optimum moisture content (OMC). In addition, multiple variable linear regression was used to analyze laboratory data in order to obtain an empirical relationship that can be used to predict the unconfined compressive strength (UCS) of a PFA-cement-sand mixture. The accuracy of the model was verified using statistical indices. The first objective of this study was to assess the effects of PFA content on the UCS of the mixture. The second was to investigate the impact of the OMC on the UCS. The focal point of this study was its derivation of a relationship that can be used to estimate the UCS on the basis of existing variables. The results indicated that PFA can strengthen sand in terms of the UCS and that excessive PFA in a mixture may adversely affect the UCS of a medium. Therefore, a mixture must have an optimum proportion of compounds. The OMC plays a vital role in enhancing UCS. The UCS of different mixtures can be predicted with an acceptable level of accuracy by using the relationship derived in this study.